Differentiated Digital Media in Religious Moderation Learning: A Convergence Theory Perspective - Siti Nafilatul Munawwaroh; Moh. Faizin; Abdulloh Hamid (Universitas Al-Amien Prenduan, 2026)
This study examines how differentiated digital media maximize students' absorption of dynamic values in religious moderation learning at SMAN 3 Sidoarjo through the analytical lens of Convergence Theory. The research addresses a critical pedagogical challenge: conventional, text-heavy instruction in Islamic Education often triggers cognitive resistance and fails to accommodate students' diverse learning modalities when introducing complex affective values. This study aims to analyze how the structural integration of multisensory digital devices and William Stern's Convergence Theory maximizes the formation of students' moderate religious paradigms based on their visual, auditory, and kinesthetic (VAK) learning styles. Employing a qualitative approach with a single-site descriptive case study design, data were gathered through instructional document analysis, participatory classroom observations, and semi-structured interviews with three Islamic Education teachers and fifteen selected students. The empirical findings demonstrate that the systemic integration of differentiated digital media, including infographics, short documentary videos, and hands-on multimedia projects, strengthens students' emotional resonance and forms an inclusive religious worldview. From the perspective of Convergence Theory, this study reveals a novel paradigm: differentiated digital media function as structured environmental stimuli (empiricism) that dynamically interact with students' innate digital-native traits (nativism) to maximize critical consciousness and theological tolerance. By bridging developmental psychology and digital instruction, these findings contribute to a framework for understanding how adaptive, personalized, and inclusive differentiated pedagogy shapes tolerant and moderate perspectives among Generation Z learners.